2008
DOI: 10.1088/0022-3727/41/23/235408
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation of 2D crumpled wires

Abstract: Abstract.When a single long piece of elastic wire is injected trough channels into a confining two-dimensional cavity, a complex structure of hierarchical loops is formed. In the limit of maximum packing density, these structures are described by several scaling laws. In this paper it is investigated this packing process but using plastic wires which give origin to completely irreversible structures of different morphology. In particular, it is studied experimentally the plastic deformation from circular to ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In the past decade, the crumpling of thin wires has been studied in two dimensions experimentally by Donato et al (2002Donato et al ( , 2003Donato et al ( , 2006; Donato and Gomes (2007); Gomes et al (2008b) followed by numerical simulations by Stoop et al (2008), from a primarily physical perspective. It wasn't until very recently that experiments were extended to three dimensions (Gomes et al, 2008a;Stoop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the crumpling of thin wires has been studied in two dimensions experimentally by Donato et al (2002Donato et al ( , 2003Donato et al ( , 2006; Donato and Gomes (2007); Gomes et al (2008b) followed by numerical simulations by Stoop et al (2008), from a primarily physical perspective. It wasn't until very recently that experiments were extended to three dimensions (Gomes et al, 2008a;Stoop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Åström et al [8] reported a divergence in F when the volume fraction of the sample is around 0.75, at which point the elastic behavior turns out to be sim-ilar to that of a granular media. In the last decade, scientists have performed many experiments to determine the dimension D of elastic and plastoelastic crumpled structures [9,10,11,12]. Most were based on the scaling relation in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The injection of filaments into cavities is a basic problem involving elasticity and self-exclusion. These are two aspects of great importance in nature, with wide range of influence from polymeric packing [1,2] to DNA packaging in viral capsids [3,4,5,6]. The structures formed by the confinement of wires packaged [3,7] and crumpled surfaces [8] present anomalous characteristics [3] that are of interest to soft matter physics and statistical physics.…”
Section: Introductionmentioning
confidence: 99%
“…These are two aspects of great importance in nature, with wide range of influence from polymeric packing [1,2] to DNA packaging in viral capsids [3,4,5,6]. The structures formed by the confinement of wires packaged [3,7] and crumpled surfaces [8] present anomalous characteristics [3] that are of interest to soft matter physics and statistical physics. The mechanical properties are influenced by the hierarchy of its folds [9,10] and show a behavior similar to that found in unbranched polymers diluted in a solvent [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation